Utilizing the same incision for staged renal transplant in patients with polycystic kidney disease requiring hand‐assisted laparoscopic nephrectomy. Issue 11 (20th September 2022) - Huynh, Nguyen; Yoon, Peter; Hort, Amy; Yao, Jinna; Lee, Taina; Yuen, Lawrence; Laurence, Jerome Martin; Pleass, Henry
Abstract: Backgrounds: Many autosomal dominant polycystic kidney disease (ADPKD) patients undergo nephrectomy and subsequent renal transplantation. We report our outcomes after hand‐assisted laparoscopic nephrectomy (HALN) where a Rutherford‐Morrison incision is used as a hand‐port site and kidney extraction site, as well the future incision site for staged transplantation. Methods: A retrospective review was performed on all adult nephrectomies for ADPKD by the Transplant Surgery department at Westmead Hospital between June 2011 and June 2021. Outcomes were compared between HALN, laparoscopic nephrectomy (LN) and open nephrectomy (ON) including operation time, hospital length of stay (LOS), post‐operative complications, subsequent transplantation and post‐transplantation wound complications. Results: Twenty‐two HALN, 8 LN and 5 ON were performed during the study period. Median kidney weights for HALN, LN and ON were significantly different (1575, 403, 3420 g respectively, P = 0.001). There was a significant difference in LOS between the HALN and ON (5.8 versus 9.8 days, P = 0.04), but not between HALN and LN (5.8 versus 5.1, P = 0.06). There was no significant difference for operation time ( P = 0.34) and major complication rates ( P = 0.58). There were 8 HALN, 5 LN and 2 ON who have had subsequent renal transplantation with one wound complication, an incisional hernia in the HALN group. Conclusion: Our HALN is associated with a shorter LOS and similar complication rate to ON and can be efficiently performed for significantly larger kidneys than LN without a significant difference in operation time or LOS. The same Rutherford‐Morrison incision site can be used for transplantation. Abstract : We report our outcomes after hand‐assisted laparoscopic nephrectomy (HALN) where a Rutherford‐Morrison incision is used as a hand‐port site and kidney extraction site, as well the future incision site for staged transplantation. Our HALN is associated with a shorter length of stay and similar complication rate to open nephrectomy and can be efficiently performed for significantly larger kidneys than laparoscopic nephrectomy without a significant difference in operation time or length of stay. The same Rutherford‐Morrison incision site can be used for transplantation.